LAND USE PLANNING FOR ARABICA COFFEE PLANTATIONS USING FUZZY LOGIC METHOD IN TANAH DATAR DISTRICT - res Ti Ana; febriandi febriandi (JURNAL BUANA, 2025)
Tanah Datar Regency generally has a physical description of land that is suitable for growing Arabica coffee plantations. But this commodity has never been planted even though the market price is much higher. This land suitability research uses fuzzy logic method. Each land indicator is considered to have a possibility with a value range of 0 to 1. This allows land indicators to collaborate with other indicators to create more precise conformity values. The suitability of arabica coffee plantation land in Tanah Datar Regency has two suitability classes, namely, "less suitable with an area of 2,118,719.5 Ha and a class of "quite suitable" covering an area of 12,691.87 Ha.